"The ice has gone": Vernacular meteorology, fisheries and human–ice relationships on Sakhalin Island. (28th June 2021) - Mamontova, Nadezhda
Abstract: This paper examines vernacular weather observations amongst rural people on Sakhalin, Russia's largest island on the Pacific Coast, and their relationship to the ice. It is based on a weather diary (2000–2016) of one of the local inhabitants and fieldwork that the author conducted in the settlement of Trambaus in 2016. The diary as a community-based weather monitoring allows us to examine how people understand, perceive and deal with the weather both daily and in the long-term perspective. Research argues that amongst all natural phenomena, the ice is the most crucial for the local inhabitants as it determines human subsistence activities, navigation and relations with other environmental forces and beings. People perceive the ice as having an agency, engage in a dialogue with it, learn and adjust themselves to its drifting patterns. Over the past decade, the inability to predict the ice's behaviour has become a major problem affecting people's well-being in the settlement. The paper advocates further integrating vernacular weather observations and their relations with natural forces into research on climate change and local fisheries management policies.